Curricularização da extensão: Projeto Comunitário nos cursos de Graduação do Centro Universitário- Católica de Santa Catarina em Jaraguá do Sul - Santos, Ana Paula Fliegner dos (2017)
Educating a new professional is a challenge posed to the universities of today, because, in addition to technical education, it is necessary to graduate ethical, human and solidarity citizens who are protagonists in the restructuring of society, in order to transform the social reality. The objective of this research, inserted in the Public Policies and Educational and Curricular Reforms Research Group of the Pontifícia Universidade Católica de São Paulo, was to analyze the impacts of the insertion of the curricular component: Community Project (CP) in the curricular matrices of the Undergraduate courses of the Centro Universitário – Católica de Santa Catarina. The CP involves students in social projects in the local reality, with different audiences. The research was based on the qualitative approach, and had as place of research the municipality of Jaraguá do Sul, the city that is the headquarters of the Centro Universitário – Católica de Santa Catarina, a community institution with a 43-year history. The documents used for documentary analysis were: Institutional Development Plan, Regulation of the Community Project Discipline, Extension Policy, Extension Program, Extension Report and Community Project (CP), of 2014, Manual of the responsible and the university students statements present in the self-assessments answered at the conclusion of the CP in 2014. In order to deepen the statements, the focus group technique was used with 10 students. The theoretical reference was drawn from Menezes (2011), Síveres (2011) and the contribution of authors who place themselves in the same spectrum of attention to the education of students who engage in social actions in the university environment: Freire (1983, 2006), in the core of the conception of an autonomous and transforming university; Gurgel (1986), Freire (1977), Nogueira (2005) and documents of FORPROEX (1998, 2006, 2012), that present the trajectory of university extension in Brazil and its conceptions; Chizzotti (2000) and Abramowicz (1996), which allow to broaden the scope of interpretation of the data present in the documents and in the self-assessments analyzed. The categories were created based on Franco (2012). Gatti (2012) underlies the focus group technique used in the research. As results, we present the impacts on the education of the subjects when experiencing social projects in their undergraduate studies, which, in turn, significantly contribute to the human and solidarity education of the students involved. We believe that the curricularisation of the extension should be part of the education of all students, regardless of their course or area of activity. We observed that education in human and social values significantly contributes to the human, social and professional education for the exercise of the profession in a conscious and civic manner